Laminate and thermal recording material

JP7643032B2Active Publication Date: 2025-03-11TOYO INK MFG CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020207852
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-15
Publication Date
2025-03-11
Estimated Expiration
2040-12-15

AI Technical Summary

Benefits of technology

【0017】 本発明により、10μm以下程度の薄膜においてあらゆる角度からの良好な発色性と、コロイド結晶層由来の鮮やかな反射光との両方を有し、保存安定性、基材密着性、耐ラビング性等の膜耐性に優れ、さらに、熱によって色が変化する感熱記録体としても利用可能な積層体を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643032000013
    Figure 0007643032000013
  • Figure 0007643032000014
    Figure 0007643032000014
  • Figure 0007643032000001
    Figure 0007643032000001
Patent Text Reader

Abstract

To provide a laminate which has both good color development property from any angle and clear reflected light derived from a colloidal crystal layer in a thin film of approximately 10 μm or less, is excellent in film resistance such as storage stability, base material adhesion and rubbing resistance, and is also available as a thermosensitive recording body whose color changes by heat.SOLUTION: A laminate is obtained by laminating a base material, a primer layer, and a colloidal crystal layer in this order, in which the colloidal crystal layer has such a structure that core-shell type resin fine particles are arrayed and a gap, and contains a chromatic color pigment.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate comprising a colloidal crystal layer, and more specifically to a laminate having excellent color development, film resistance and heat sensitivity by combining a primer layer with a colloidal crystal layer made of core-shell type resin fine particles and having a chromatic dye. [Background technology]

[0002] Photonic crystals are artificial crystals with nano-periodic structures in which materials with different refractive indices are arranged at intervals equivalent to the wavelength of light, and have been actively studied in recent years due to their various interesting optical properties, such as the reflection of light of a specific wavelength known as Bragg reflection, and the light trapping and light amplification effects due to photonic band gaps. Among them, colloidal crystals, which are made by regularly arranging monodispersed particles, are photonic crystals that can be produced relatively easily, but due to issues in the arrangement of particles and their fixation, mass production technology that can easily produce them has not yet been established. In addition, the hue of colloidal crystals is determined by the particle diameter and the distance between the particles, but there are problems such as a narrow range of hues and difficulty in reproducing colors.

[0003] Patent Document 1 discloses a method of dispersing colloidal particles and a colorant in a dispersion medium component made of a hydrophilic monomer by ultrasonic waves, forming a three-dimensional regular array of colloidal particles, and then hardening and polymerizing the dispersion medium component to obtain a fixed colloidal crystal. However, this method reduces the difference in refractive index between the colloidal particles and the matrix (polymer used in the dispersion medium), and sufficient color development cannot be obtained in a thin film of about 10 μm or less.

[0004] Patent Documents 2 and 3 disclose coatings of colloidal crystals in which the shells of core-shell type resin particles are partially fused and bound together. These coatings have improved coating resistance compared to particles with a single structure, but they cannot simultaneously achieve film resistance such as substrate conformity when folded, substrate adhesion, abrasion resistance, water resistance, and solvent resistance. In addition, since they do not contain chromatic coloring matter, there is a problem that the angle range in which color development can be seen is narrow, which is a problem specific to colloidal crystals, and they are not suitable for design applications. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2008-309933 A [Patent Document 2] JP 2001-329197 A [Patent Document 3] JP 2008-083545 A Summary of the Invention [Problem to be solved by the invention]

[0006] The problem to be solved by the present invention is to provide a laminate which, in a thin film of about 10 μm or less, has both good color development from all angles and vivid reflected light derived from the colloidal crystal layer, and which has excellent storage stability, adhesion to substrates, and film resistance such as rubbing resistance, and which can also be used as a thermal recording medium whose color changes when exposed to heat. [Means for solving the problem]

[0007] As a result of extensive investigations, the present inventors have found that a laminate satisfying the configuration of the present invention can solve the above-mentioned problems.

[0008] A laminate according to one aspect of the present invention is a laminate comprising a substrate, a primer layer, and a colloidal crystal layer laminated in this order, the colloidal crystal layer having a structure in which core-shell type resin particles are arranged and voids, and containing a chromatic color dye.

[0009] A laminate according to another embodiment of the present invention is characterized in that the core-shell type resin fine particles contain a shell in the range of 10 to 150% by mass relative to the mass of the core.

[0010] A laminate according to another aspect of the present invention is characterized in that the core has a glass transition point of 60°C or higher, and the shell has a glass transition point in the range of -50 to 20°C.

[0011] A laminate according to another aspect of the present invention is characterized in that the primer layer is a layer containing at least one resin selected from the group consisting of acrylic resins and urethane resins.

[0012] A laminate according to another aspect of the present invention is characterized in that the resin has a glass transition point in the range of -30 to 70°C.

[0013] A laminate according to another aspect of the present invention is characterized in that the colloidal crystal layer contains the chromatic dye in a range of 0.01 to 30% by mass, based on the mass of the core-shell resin fine particles.

[0014] In a laminate according to another aspect of the present invention, the chromatic colorant is an organic pigment.

[0015] A laminate according to another embodiment of the present invention is characterized in that the colloidal crystal layer further contains colorless black fine particles.

[0016] A thermosensitive recording medium according to another aspect of the present invention is characterized in that it is made using the above laminate. Effect of the Invention

[0017] The present invention can provide a laminate that has both good color development from all angles in a thin film of about 10 μm or less and vivid reflected light derived from the colloidal crystal layer, and that is excellent in storage stability, adhesion to substrates, and film resistance such as rubbing resistance, and further that can be used as a thermal recording medium whose color changes when exposed to heat. [Brief description of the drawings]

[0018] [Figure 1] FIG. 2 is a diagram illustrating a stack according to an embodiment of the present invention. [Diagram 2] FIG. 13 is a diagram showing a state in which the color of the colloidal crystal layer has faded after heating the laminate according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] <Laminate> The laminate of the present invention is characterized in that a substrate, a primer layer, and a colloidal crystal layer are laminated in this order, and the colloidal crystal layer has a structure in which core-shell type resin particles are arranged, has voids, and contains a chromatic dye. By containing a chromatic dye in the colloidal crystal layer, it is possible to obtain a laminate that has both vivid coloring from any angle and vivid reflected light seen at a specific angle due to the colloidal crystal layer. In addition, it is possible to achieve excellent design properties and film resistance. In this specification, a configuration that is viewed from the colloidal crystal layer side of the laminate may be referred to as "front printing," and a configuration that is viewed from the substrate side may be referred to as "reverse printing."

[0020] Furthermore, the laminate of the present invention exhibits a clear color change when heat is applied, and therefore can be used as a thermal recording medium such as a thermal recording sheet. The colloidal crystal layer in the laminate of the present invention has a densely packed structure of core-shell type resin particles, and the shells of the core-shell type resin particles are fused and bonded to each other while leaving voids, as shown in Figure 1. The laminate of the present invention exhibits a vivid structural color even in a thin film because of the large difference in refractive index between the core-shell type resin particles and the voids. On the other hand, when this laminate is heated by applying a certain amount of thermal energy, the shells of the core-shell resin particles flow and fill the voids, forming a loosely packed structure as shown in Figure 2. In such a loosely packed structure, the difference in refractive index between the core particles and the matrix becomes small, so that the thin film does not show a structural color and becomes a semi-transparent layer, allowing the color of the layer below the colloidal crystal layer to be visually recognized. Hereinafter, an embodiment of the present invention will be described in detail.

[0021] <Primer layer> The primer layer in the present invention is provided between the substrate and the colloidal crystal layer, and serves to suppress interfacial peeling between the substrate and the colloidal crystal layer. By providing the primer layer, the adhesion to the colloidal crystal layer is improved, and a laminate having excellent substrate conformability, abrasion resistance, water resistance, etc. can be obtained. The primer layer is preferably insoluble in water. The resin forming the primer layer is not particularly limited and can be appropriately selected according to the type of the substrate or colloidal crystal layer. Preferably, it contains at least one resin selected from the group consisting of acrylic resin, urethane resin, polyolefin resin, polyester resin, and composite resin obtained by combining these resins. Among them, it preferably contains at least one resin selected from the group consisting of acrylic resin and urethane resin, more preferably contains acrylic resin, and further preferably contains acrylic resin containing styrene as a constituent unit (hereinafter, styrene acrylic resin). The use of acrylic resin is preferable because it provides excellent adhesion to the substrate or colloidal crystal layer, excellent substrate conformability and water resistance of the primer layer, and good substrate conformability, abrasion resistance, and water resistance of the laminate. These resins may be used alone or in combination of two or more.

[0022] From the viewpoint of suppressing the influence on the colloidal crystal layer, the resin forming the primer layer preferably has a low content of unreacted components and residual solvent, and an aqueous resin is preferably used. Here, the aqueous resin refers to a resin that can be dispersed or dissolved in an aqueous medium, and the aqueous medium includes water or a dispersion medium or solvent that can be miscible with water.

[0023] When the resin forming the primer layer is an aqueous resin, the method for producing the aqueous resin is not particularly limited. From the viewpoint of obtaining a resin with low viscosity, high solid content and high molecular weight, an emulsion polymerization method is preferable.

[0024] [Acrylic resin] When the resin constituting the primer layer is an aqueous acrylic resin, the aqueous acrylic resin can be obtained by emulsion polymerization of an ethylenically unsaturated monomer including a (meth)acrylic monomer.

[0025] {Ethylenically unsaturated monomer} Examples of ethylenically unsaturated monomers that can be used in the production of the above-mentioned aqueous acrylic resin include styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, m-methylstyrene, vinylnaphthalene, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxytetraethylene glycol (meth)acrylate, phenoxyhexaethylene glycol (meth)acrylate, and phenoxyhexaethylene glycol (meth)acrylate. aromatic ethylenically unsaturated monomers such as phenyl (meth)acrylate; methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, heptyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, Ethylenically unsaturated monomers containing a straight or branched alkyl group, such as silyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, and behenyl (meth)acrylate; cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, 1-adamantyl (meth)acrylate, and the like. ethylenically unsaturated monomers containing an alicyclic alkyl group, such as trifluoroethyl (meth)acrylate and heptadecafluorodecyl (meth)acrylate; ethylenically unsaturated monomers containing a fluorinated alkyl group, such as trifluoroethyl (meth)acrylate and heptadecafluorodecyl (meth)acrylate; ethylenically unsaturated monomers containing a carboxy group, such as (anhydrous) maleic acid, fumaric acid, itaconic acid, citraconic acid, or their alkyl or alkenyl monoesters, succinic acid β-(meth)acryloxyethyl monoester, acrylic acid, methacrylic acid, crotonic acid, cinnamic acid, etc.Sulfo group-containing ethylenically unsaturated monomers such as 2-acrylamido 2-methylpropanesulfonate sodium, methallylsulfonic acid, methallylsulfonic acid, sodium methallylsulfonate, allylsulfonic acid, sodium allylsulfonate, ammonium allylsulfonate, and vinylsulfonic acid; (meth)acrylamide, N-methoxymethyl-(meth)acrylamide, N-ethoxymethyl-(meth)acrylamide, N-propoxymethyl-(meth)acrylamide, N-butoxymethyl-(meth)acrylamide, N-pentoxymethyl-(meth)acrylamide, N,N-di(methoxymethyl)acrylamide, N-ethoxymethyl-N-methoxymethylmethacrylamide, N,N-di(ethoxymethyl)acrylamide, N-ethoxymethyl-N-propoxymethylmethacrylamide, N,N-di(propoxymethyl)acrylamide, N-butoxymethyl-N-(propoxymethyl)methacrylamide, N,N-di(butoxymethyl)acrylamide, ethylenically unsaturated monomers containing an amide group, such as N-butyl-N-(methoxymethyl)acrylamide, N,N-di(pentoxymethyl)acrylamide, N-methoxymethyl-N-(pentoxymethyl)methacrylamide, N,N-dimethylaminopropylacrylamide, N,N-diethylaminopropylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, and diacetone acrylamide; ethylenically unsaturated monomers containing a hydroxyl group, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, glycerol mono(meth)acrylate, 4-hydroxyvinylbenzene, 1-ethynyl-1-cyclohexanol, and allyl alcohol; ethylenically unsaturated monomers containing a polyoxyethylene group, such as methoxypolyethylene glycol (meth)acrylate and polyethylene glycol (meth)acrylate;Examples of the ethylenically unsaturated monomer include dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, methylethylaminoethyl (meth)acrylate, dimethylaminostyrene, and diethylaminostyrene. Examples of the ethylenically unsaturated monomer include amino group-containing ethylenically unsaturated monomers such as dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, and methylethylaminoethyl (meth)acrylate; and epoxy group-containing ethylenically unsaturated monomers such as glycidyl (meth)acrylate and 3,4-epoxycyclohexyl (meth)acrylate. ethylenically unsaturated monomers containing a ketone group, such as diacetone (meth)acrylamide and acetoacetoxy (meth)acrylate; allyl (meth)acrylate, 1-methylallyl (meth)acrylate, 2-methylallyl (meth)acrylate, 1-butenyl (meth)acrylate, 2-butenyl (meth)acrylate, 3-butenyl (meth)acrylate, 1,3-methyl-3-butenyl (meth)acrylate, 2-chloroallyl (meth)acrylate, 3-chloroallyl (meth)acrylate, o-allylphenyl (meth)acrylate acrylate, 2-(allyloxy)ethyl (meth)acrylate, allyl lactyl (meth)acrylate, citronellyl (meth)acrylate, geranyl (meth)acrylate, rosinyl (meth)acrylate, cinnamyl (meth)acrylate, diallyl maleate, diaryl itaconic acid, vinyl (meth)acrylate, vinyl crotonate, vinyl oleate, vinyl linoleate, 2-(2'-vinyloxyethoxy)ethyl (meth)acrylate, ethylene glycol di(meth)acrylate, triethylene glycol (meth)acrylate ethylenically unsaturated monomers having two or more ethylenically unsaturated groups, such as ethylenically unsaturated acrylate, tetraethylene glycol (meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, 1,1,1-trishydroxymethylethane diacrylate, 1,1,1-trishydroxymethylethane triacrylate, 1,1,1-trishydroxymethylpropane triacrylate, divinylbenzene, divinyl adipate, diallyl isophthalate, diallyl phthalate, and diallyl maleate;Examples of the ethylenically unsaturated monomers include alkoxysilyl groups such as γ-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropyltributoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-acryloxypropyltriethoxysilane, 3-acryloxypropylmethyldimethoxysilane, 3-methacryloxymethyltrimethoxysilane, 3-acryloxymethyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltributoxysilane, and vinylmethyldimethoxysilane; and ethylenically unsaturated monomers containing methylol groups such as N-methylol(meth)acrylamide, N,N-dimethylol(meth)acrylamide, and alkyl etherified N-methylol(meth)acrylamide. These monomers may be used alone or in combination of two or more.

[0026] The above ethylenically unsaturated monomer may have a reactive group for the purpose of crosslinking between the primer layer and the core-shell type resin fine particles that form the colloidal crystal layer. The reactive group that may be included includes, for example, an epoxy group, a carboxy group, a hydroxyl group, a ketone group, and a hydrazide group, and is more preferably a ketone group. In particular, when the reactive group is a ketone group and the crosslinking agent is a hydrazide crosslinking agent, a ketone-hydrazide crosslink can be formed. In addition, when the aqueous acrylic resin is a resin fine particle that can be dispersed in an aqueous medium, if an ethylenically unsaturated monomer having a highly hydrophilic ketone group is used in the copolymerization composition, the ketone group is introduced to the outside of the resin fine particle, i.e., near the interface with the aqueous medium, and is considered to be able to efficiently form a crosslink with the hydrazide crosslinking agent.

[0027] When the aqueous acrylic resin contains a ketone group, the preferred content of the ketone group is in the range of 0.05 to 0.3 mmol / g based on the mass of the aqueous acrylic resin. By introducing the ketone group in the range of 0.05 to 0.3 mmol / g, crosslinking is formed without inhibiting the fusion of the aqueous acrylic resin, so that the primer layer and the colloidal crystal layer are more firmly bonded. This further improves the conformability of the colloidal crystal coating film, and a laminate with good adhesion and abrasion resistance can be obtained.

[0028] {Radical polymerization initiator} As the radical polymerization initiator used in the production of the aqueous acrylic resin, a known oil-soluble polymerization initiator or water-soluble polymerization initiator can be used. These may be used alone or in combination of two or more. The oil-soluble polymerization initiator is not particularly limited, and examples thereof include organic peroxides such as benzoyl peroxide, tert-butyl peroxybenzoate, tert-butyl hydroperoxide, tert-butyl peroxy(2-ethylhexanoate), tert-butylperoxy-3,5,5-trimethylhexanoate, and di-tert-butyl peroxide; and azobis compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis-2,4-dimethylvaleronitrile, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), and 1,1'-azobis-cyclohexane-1-carbonitrile. In the emulsion polymerization, it is preferable to use a water-soluble polymerization initiator. As the water-soluble polymerization initiator, for example, conventionally known ones such as ammonium persulfate (APS), potassium persulfate (KPS), hydrogen peroxide, and 2,2'-azobis(2-methylpropionamidine) dihydrochloride can be suitably used.

[0029] {Surfactant} A surfactant is generally used in the production of an aqueous acrylic resin, and the use of the surfactant can improve the stability and monodispersity of the core-shell type resin microparticles. The surfactant can be an anionic or nonionic surfactant, and is preferably an anionic surfactant. These surfactants can be used alone or in combination of two or more kinds. Examples of the surfactant include anionic reactive surfactants, anionic non-reactive surfactants, nonionic reactive surfactants, and nonionic non-reactive surfactants. Here, the reactive surfactant refers to a surfactant that can be polymerized with the above-mentioned ethylenically unsaturated monomer. More specifically, it means a surfactant having a reactive group that can polymerize with an ethylenically unsaturated bond. Examples of the reactive group include alkenyl groups such as vinyl groups, allyl groups, and 1-propenyl groups, and (meth)acryloyl groups. By using a reactive surfactant, the amount of free surfactant components contained in the aqueous acrylic resin is reduced, and adverse effects on the particle arrangement of the colloidal crystals are suppressed, making it possible to obtain a laminate with superior color development properties.

[0030] {Other ingredients} In the production of the aqueous acrylic resin, a reducing agent, a buffering agent, a chain transfer agent, and a neutralizing agent can be used as necessary.

[0031] [Urethane resin] When the resin forming the primer layer is an aqueous urethane resin, the aqueous urethane resin is not particularly limited. The aqueous urethane resin can be obtained, for example, by dispersing the urethane resin obtained by polyaddition reaction of any polyol and polyisocyanate in a non-aqueous system in water using a surfactant, or by introducing a hydrophilic group such as a carboxyl group into the urethane resin to emulsify it by itself. The aqueous urethane resin may be reacted with a diamine or a dihydrazide compound to introduce a functional group to the end of the isocyanate group, or may be chain-extended to increase the molecular weight. The aqueous urethane resin may be composited with a different resin by, for example, grafting an acrylic resin skeleton or an olefin resin skeleton via a reactive group.

[0032] Examples of polyols constituting the urethane resin include polyether polyols, polyester polyols, polycarbonate polyols, polyolefin polyols, and castor oil polyols.

[0033] Examples of polyether polyols include polyethylene glycol, polypropylene glycol, poly(ethylene / propylene) glycol, and polytetramethylene glycol.

[0034] Examples of polyester polyols include reaction products of difunctional or trifunctional polyols and dibasic acids. Examples of difunctional polyols include ethylene glycol, propylene glycol, dipropylene glycol, diethylene glycol, triethylene glycol, butylene glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 3,3'-dimethylolheptane, polyoxyethylene glycol, polyoxypropylene glycol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, octanediol, butylethylpentanediol, 2-ethyl-1,3-hexanediol, cyclohexanediol, and bisphenol A. Examples of trifunctional polyols include glycerin, trimethylolpropane, and pentaerythritol. Examples of dibasic acids include terephthalic acid, adipic acid, azelaic acid, sebacic acid, dimer acid, hydrogenated dimer acid, phthalic anhydride, isophthalic acid, and trimellitic acid.

[0035] Examples of the polycarbonate polyol include reaction products of the above-mentioned bifunctional polyols with dialkyl carbonates, alkylene carbonates, and diaryl carbonates.

[0036] Examples of polyolefin polyols include hydroxyl group-containing polybutadiene, acid group-containing hydrogenated polybutadiene, hydroxyl group-containing polyisoprene, hydroxyl group-containing hydrogenated polyisoprene, hydroxyl group-containing chlorinated polypropylene, and hydroxyl group-containing chlorinated polyethylene.

[0037] Examples of polyisocyanates that make up urethane resins include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylylene diisocyanate, lysine diisocyanate, 3,3'-dimethyl-4,4'-biphenylene diisocyanate, 3,3'-dimethoxy-4,4'-biphenylene diisocyanate, 3,3'-dichloro-4,4'- Examples of the polyisocyanates include aromatic polyisocyanates such as biphenylene diisocyanate, 1,5-naphthalene diisocyanate, and 1,5-tetrahydronaphthalene diisocyanate; aliphatic polyisocyanates such as tetramethylene diisocyanate, hexamethylene diisocyanate, and trimethylhexamethylene diisocyanate; and alicyclic polyisocyanates such as isophorone diisocyanate, 1,4-cyclohexylene diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate.

[0038] In the synthesis of the urethane resin, a low molecular weight diol may be used in combination for the purpose of adjusting the urethane bond concentration and introducing various functional groups. The low molecular weight diol is preferably a diol having a molecular weight of 500 or less, and examples thereof include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, pentanediol, hexanediol, octanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,4-butylenediol, dipropylene glycol, glycerin, trimethylolpropane, trimethylolethane, 1,2,6-butanetriol, pentaerythritol, sorbitol, N,N-bis(2-hydroxypropyl)aniline, dimethylol alkanoic acids such as dimethylolacetic acid, dimethylolpropionic acid, dimethylolbutanoic acid, 2,2-dimethylolbutyric acid, and 2,2-dimethylolpentanoic acid, dihydroxysuccinic acid, dihydroxypropionic acid, and dihydroxybenzoic acid.

[0039] Examples of compounds that can be used for the terminal modification or chain extension reaction include diamines such as hydrazine, ethylenediamine, propylenediamine, hexamethylenediamine, nonamethylenediamine, xylylenediamine, isophoronediamine, piperazine and its derivatives, phenylenediamine, tolylenediamine, xylylenediamine, and N-(β-aminoethyl)ethanolamine, and dihydrazides such as adipic acid dihydrazide and isophthalic acid dihydrazide.

[0040] Examples of commercially available aqueous urethane resins include the Superflex series (SF-170, SF-210, etc.) manufactured by Daiichi Kogyo Seiyaku, the U-coat and Permalin series (UX-310, UX-3945, etc.) manufactured by Sanyo Chemical Industries, Ltd., the Yuriano series (W-600, W-321, etc.) manufactured by Arakawa Chemical Industry Co., Ltd., the Adeka Pontitor series (HUX-420A, HUX-386, etc.) manufactured by ADEKA, the UW series (UW-5002, UW-5020, etc.) manufactured by Ube Industries, Ltd., and the Acrit series (WBR2000U, WBR2101, WEM-200U, etc.) manufactured by Taisei Fine Chemical Co., Ltd.

[0041] [Polyolefin resin] When the resin constituting the primer layer is an aqueous polyolefin resin, the aqueous polyolefin resin may be, for example, an acid-modified polyolefin obtained by modifying a base resin such as an ethylene-propylene copolymer, a propylene-1-butene copolymer, or an ethylene-propylene-1-butene copolymer with maleic acid, etc. The polyolefin resin may be composited with a different resin, for example, by grafting an acrylic resin skeleton. The above-mentioned aqueous polyolefin resin can be used to obtain an aqueous dispersion by dispersing the resin in water using a surfactant, or by introducing a hydrophilic group into the polyolefin resin to cause self-emulsification.

[0042] Commercially available water-based polyolefin resins include, for example, the Superchron series and Auroren series (E-480T, AE-301, etc.) manufactured by Nippon Paper Industries Co., Ltd., the Arrowbase series (SB-1230N, SB-1200, etc.) manufactured by Unitika, and the Aptlock series (BW-5550, etc.) manufactured by Mitsubishi Chemical.

[0043] [Polyester resin] When the resin forming the primer layer is an aqueous polyester resin, the aqueous polyester resin is not particularly limited. The aqueous polyester resin can be obtained by reacting a difunctional or trifunctional polyol with a dibasic acid. The description of the above [urethane resin] can be used for the difunctional or trifunctional polyol and the dibasic acid. The aqueous polyester resin can be prepared as an aqueous dispersion by dispersing the resin in water using a surfactant, or by introducing a hydrophilic group into the polyester resin to emulsify it by itself. Commercially available aqueous polyester resins include, for example, the Pluscoat series (Z-730, Z-760, etc.) manufactured by GOO Chemical Co., Ltd.

[0044] The resin forming the primer layer in the present invention preferably has a glass transition point (Tg) in the range of -30 to 70°C. By having a glass transition point in the above range, excessive intrusion of the primer component into the voids of the colloidal crystal layer is suppressed, and good structural color can be maintained for a long period of time. In addition, wettability with the substrate and the surface of the core-shell type resin fine particles is improved, resulting in excellent adhesion. In addition, fusion between the primer layer and the shells of the core-shell type resin fine particles is promoted, resulting in excellent strength of the bonded portion. As a result, the obtained laminate has excellent color development, storage stability, and various resistances (abrasion resistance, substrate followability). The resin preferably has a glass transition point in the range of −30 to 20° C., and may have a plurality of glass transition points. The glass transition point in this specification can be determined by using a DSC (differential scanning calorimeter).

[0045] The resin forming the primer layer preferably has a carboxy group. The acid value of the resin is preferably in the range of 5 to 70 mgKOH / g. When the acid value is in the above range, the adhesion between the primer layer and the substrate is improved. In addition, the adhesion between the colloidal crystal layer and the primer layer is also good. Furthermore, the primer layer is prevented from swelling or dissolving due to moisture or the like, which would cause the regular arrangement of the colloidal crystals to be disrupted. As a result, the obtained laminate exhibits excellent color development, and can maintain the excellent color development even after aging tests and various resistance tests under high temperature and high humidity conditions.

[0046] [Formation of primer layer] The method for forming the primer layer is not particularly limited. For example, the primer layer can be formed by applying a primer composition containing an aqueous resin and water that forms the primer layer onto a substrate, and drying the applied composition as necessary. The thickness of the primer layer is not particularly limited, and from the viewpoint of the function expression of the primer layer and productivity, it is preferably 1 to 50 μm, more preferably 2 to 20 μm, and even more preferably 2 to 10 μm. When the thickness of the primer layer is 1 μm or more, the binding between the primer layer and the substrate layer and between the primer layer and the colloidal crystal layer is improved, and the laminate has excellent substrate conformability, abrasion resistance, and water resistance. The thickness of each layer in this specification can be measured by observing a cross section of the laminate using a scanning electron microscope. The primer composition may contain various additives, such as hydrophilic solvents, achromatic black fine particles, chromatic dyes, photothermal conversion agents, and crosslinking agents, for the purpose of improving coatability, color development of the laminate, sensitivity to color change, and film resistance, within the scope of not adversely affecting the various physical properties of the laminate.

[0047] {hydrophilic solvent} Examples of the hydrophilic solvent include monohydric alcohol solvents such as ethanol, 1-propanol, and isopropyl alcohol; glycol solvents such as ethylene glycol, 1,3-propanediol, and propylene glycol; glycol ether solvents such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, diethylene glycol monobutyl ether, and triethylene glycol monoethyl ether; lactam solvents such as N-methyl-2-pyrrolidone, N-hydroxyethyl-2-pyrrolidone, and ε-caprolactam; and amide solvents such as formamide and N-methylformamide.

[0048] {Achromatic black particles} The achromatic black fine particles absorb the scattered light in the laminate to make the color more clear. As the achromatic black fine particles, black dyes or pigments can be used, and carbon black is preferred from the viewpoint of having little effect on the reflection spectrum shape in the visible region and excellent durability such as weather resistance. The carbon black may be either a dispersion type dispersed in water using a dispersant or a self-dispersion type, but it is preferable to use self-dispersion type carbon black from the viewpoint of not affecting the arrangement of the fine particles by the dispersant.

[0049] {Chromatic pigment} The chromatic dye plays a role of exhibiting good color development from all angles in the thin film and absorbing scattered light in the laminate to make the reflected light from the colloidal crystal clear. At least one selected from the group consisting of pigments and dyes can be used as the chromatic dye, and from the viewpoint of film resistance, pigments are preferred. As the pigment that can be used in the present invention, known organic pigments, inorganic pigments, fluorescent pigments, etc. can be used. Examples of organic pigments include azo-based, phthalocyanine-based, anthraquinone-based, perylene-based, perinone-based, quinacridone-based, thioindigo-based, dioxazine-based, isoindolinone-based, quinophthalone-based, azomethine azo-based, dicyanopyrrolopyrrole-based, and isoindoline-based pigments. Examples of inorganic pigments include aluminum particles, mica, bronze powder, chrome vermilion, yellow lead, cadmium yellow, cadmium red, ultramarine, Prussian blue, iron oxide red, yellow iron oxide, iron black, titanium oxide, and zinc oxide. The pigment may be used alone or in combination of two or more kinds. Organic pigments are preferred because they have excellent color development properties.

[0050] Examples of commercially available organic pigments include yellow pigment: LIONOL YELLOW TT-1402G (CI Pigment Yellow 14), red pigment: LIONOL RED 6B FG-4306-G (CI Pigment Red 57:1), blue pigment: LIONOL BLUE FG-7358-G (CI Pigment Blue 15:4), green pigment: LIONOL GREEN 8624 (CI Pigment Green 36), and purple pigment: LIONOGEN VIOLET FG6147G (CI Pigment Violet 23) (manufactured by Toyo Color Co., Ltd.). Examples of commercially available inorganic pigments include Todacolor 100ED and Todacolor TSY-1 (manufactured by Toda Kogyo Co., Ltd.).

[0051] As the dye, either water-based dye or oil-based dye can be used. In the case of oil-based dye, it is preferable that it is dissolved in a hydrophilic solvent. As the dye, there is no particular limitation, and examples thereof include Monascus pigment, Gardenia red pigment, Cochineal pigment, Annatto pigment, Gardenia blue pigment, Gardenia green pigment, Acid red, Acid blue, Acid yellow, Basic red, Basic blue, Basic violet, Direct red, Direct blue, Direct yellow, Direct black, Oil red, Oil blue, Oil black, and a polymer to which a pigment is bonded. Examples of commercially available products include Supermonas UR, Annatto yellow, Amethyst color RX-S, and New Green No. 1 (manufactured by Yaegaki Fermentation Engineering Co., Ltd.). Fluorescent dyes may also be used.

[0052] (Pigment dispersion method) The method of blending the pigment in the primer layer can be appropriately selected from known methods, and is preferably a method of blending the pigment as a pigment dispersion dispersed by a dispersing resin. Examples of methods for stably maintaining dispersibility include (1) a method of adsorbing a water-soluble pigment dispersing resin onto the pigment surface and dispersing the pigment, (2) a method of adsorbing a water-soluble and / or water-dispersible surfactant onto the pigment surface and dispersing the pigment, (3) a method of chemically or physically introducing a hydrophilic functional group onto the pigment surface and dispersing the pigment without a dispersing resin or surfactant (self-dispersing pigment), and (4) a method of coating the pigment with a water-insoluble resin and dispersing the pigment using another water-soluble pigment dispersing resin or surfactant as necessary. From the viewpoint of excellent pigment dispersion stability and film physical properties, (1) the method of using a water-soluble pigment dispersing resin is preferable.

[0053] (Water-soluble pigment dispersion resin) The water-soluble pigment dispersion resin is not particularly limited, and examples thereof include poly(meth)acrylic resin, styrene-(meth)acrylic resin, (anhydrous)maleic acid resin, styrene-(anhydrous)maleic acid resin, olefin-(anhydrous)maleic acid resin, polyurethane resin, polyurea resin, polyurethane urea resin, and polyester resin. The weight average molecular weight of the water-soluble pigment dispersion resin is preferably in the range of 1,000 to 300,000, more preferably in the range of 5,000 to 200,000. By having the weight average molecular weight in the above range, the pigment is stably dispersed in water and storage stability is improved. When the weight average molecular weight is 1,000 or more, when the pigment is contained in the primer layer or colloidal crystal layer, it is difficult to dissolve in water or a solvent, and the film properties such as water resistance and solvent resistance are improved. When the weight average molecular weight is 300,000 or less, the viscosity of the pigment dispersion is kept low.

[0054] {Photothermal conversion agents (excluding achromatic black particles)} The photothermal conversion agent (excluding achromatic black fine particles) serves to promote heating of the core-shell type resin fine particles in the adjacent colloidal crystal layer when the laminate is irradiated with laser light. Examples of the photothermal conversion agent include achromatic black fine particles such as carbon black and graphite, as well as cyanine dyes, croconium dyes, polymethine dyes, azulenium dyes, squarylium dyes, thiopyrylium dyes, naphthoquinone dyes, anthraquinone dyes, phthalocyanine dyes, naphthalocyanine dyes, azo dyes, thioamide dyes, dithiol dyes, and indoaniline dyes.

[0055] {Crosslinking agent} The crosslinking agent that may be contained in the primer composition is not particularly limited, and examples thereof include hydrazide compounds (polyhydrazides) having two or more hydrazino groups that react with active carbonyl groups to form keto-hydrazide crosslinks, isocyanate compounds that react with hydroxyl groups or amino groups to form urethane bonds or urea bonds, epoxy compounds that react with carboxy groups, amino groups, etc., and carbodiimide compounds, and can be appropriately selected depending on the application. For example, when the resin contained in the primer composition has a carboxyl group, crosslinking can be formed via an epoxy crosslinking agent or a carbodiimide crosslinking agent. For example, when the resin contained in the primer composition has a hydroxyl group, crosslinking can be formed via a polyisocyanate crosslinking agent. For example, when the resin contained in the primer composition has a ketone group, crosslinking can be formed via a hydrazide crosslinking agent. As the crosslinking agent, it is preferable to use a hydrazide crosslinking agent to form a ketone-hydrazide crosslink as described above. Examples of the hydrazide crosslinking agent include adipic acid dihydrazide and a water-soluble resin modified with a polyfunctional hydrazide group.

[0056] <Colloidal crystal layer> The laminate of the present invention has a colloidal crystal layer containing core-shell type resin fine particles. The colloidal crystal layer has a structure in which the core-shell type resin fine particles are regularly arranged, and therefore exhibits a structural color derived from Bragg reflection, thereby performing a color-developing function. The colloidal crystal layer also contains core-shell type resin fine particles and has a structure in which the core-shell type resin fine particles are regularly arranged. The colloidal crystal layer also contains a chromatic color dye and has voids. The core-shell type resin particles have a regular array structure, and therefore the shells of adjacent core-shell type resin particles and the shells of the core-shell type resin particles and the layer in contact with the shells can be easily bound together, thereby exhibiting good adhesive properties and various resistances. In addition, the colloidal crystal layer has voids, which increases the difference in refractive index between the particles and the voids, thereby exhibiting excellent color development properties. Furthermore, by containing a chromatic dye in the colloidal crystal layer, scattered light within the laminate is absorbed, making the reflected light originating from the colloidal crystals clear, and good coloring can be achieved from all angles in the thin film.

[0057] [Core-shell type resin particles] The core-shell type resin microparticles have a structure in which the core and shell are water-insoluble polymers and the core (inner layer) and shell (outer layer) are incompatible with each other. The core maintains the spherical shape, and the shell has fluidity and functions as a binding site. The core-shell type resin microparticles in this specification may have a multilayer structure or a gradient in composition within each of the core and shell. A composition containing core-shell type resin microparticles is applied to a substrate or the like, and as the medium such as water evaporates, the particles are transported and accumulated to be arranged in a regular pattern, and the shells of the particles are fused to each other to the extent that the voids are not filled, thereby forming a colloidal crystal layer. On the other hand, when a certain amount of heat energy is applied to the laminate, the shells flow and fill the voids in the heated areas. This causes the structural color of the colloidal crystal layer to fade, significantly changing the color of the laminate. Furthermore, the faded areas are covered by the flowing shells, which form a film with excellent flexibility, so no cracks occur. As a result, the heated laminate has excellent film durability, just like the unheated laminate.

[0058] The core-shell type resin fine particles in the present invention are not particularly limited, but are preferably polymers of ethylenically unsaturated monomers, more preferably acrylic resins, and even more preferably styrene-acrylic resins.

[0059] The method for producing core-shell type resin microparticles is not particularly limited, and includes a method of polymerizing ethylenically unsaturated monomer in an aqueous medium such as emulsion polymerization, and a phase inversion emulsification method in which polymerization is performed in a non-aqueous system and then the phase is inverted to an aqueous phase while removing the solvent, but it is preferable to use emulsion polymerization because it can achieve high molecular weight, low viscosity, and high solid content concentration.In addition, in emulsion polymerization, either two-stage polymerization in which the monomer composition is changed between the first stage and the second stage and dropped, or multi-stage polymerization in which the monomer composition is changed in three or more stages and dropped, may be used. The core-shell type resin fine particles can be prepared by the above-mentioned two-stage polymerization, specifically, by the procedure shown below. (1) First, an aqueous medium and a surfactant are charged into a reaction tank and the temperature is raised. Then, under a nitrogen atmosphere, a radical polymerization initiator is added while an emulsion of an ethylenically unsaturated monomer in the first step of forming the core is dropped. After the reaction starts, the particles gradually grow according to the amount of the drop to form the core particle. (2) Next, when the first stage of dropping is completed and the heat generation has subsided, the second stage of dropping the emulsion of the ethylenically unsaturated monomer that forms the shell is started. At this time, additional initiator may be added. The dropped second stage ethylenically unsaturated monomer is once distributed to the core particles, but as the polymerization proceeds, it precipitates as a polymer on the outer layer of the core particles to form a shell layer.

[0060] {Ethylenically unsaturated monomer} As the ethylenically unsaturated monomer that can be used in the production of the core-shell type resin particles, the description in the section on <Ethylenically unsaturated monomer> in the above <Primer layer> can be used. The ethylenically unsaturated monomer forming the core particle preferably contains an aromatic ethylenically unsaturated monomer in the range of 70 to 100% by mass based on the total mass of the ethylenically unsaturated monomer forming the core particle. By containing the aromatic ethylenically unsaturated monomer in the above range, the refractive index of the core portion increases, the difference in refractive index between the particle portion and the air gap portion in the colloidal crystal increases, and the color development of the colloidal crystal layer improves. In addition, the contrast between the core portion and the shell portion becomes clear, and the shell portion can be sufficiently fused. This allows the film resistance and color development to be better maintained.

[0061] The ethylenically unsaturated monomer may also have a reactive group for the purpose of forming crosslinks within the colloidal crystal layer and between the colloidal crystal layer and a layer in contact with the colloidal crystal layer. By forming crosslinks within the colloidal crystal layer and between the colloidal crystal layer and a layer in contact with the colloidal crystal layer, the coating resistance of the resulting laminate is improved.

[0062] Crosslinking within the colloidal crystal layer and between the colloidal crystals and a layer in contact with the colloidal crystal layer can be introduced by a method of reacting reactive groups of the core-shell type resin microparticles with each other, a method of reacting reactive groups of the core-shell type resin microparticles with reactive groups in a primer layer, an adhesive layer or a resin layer described below, a method of crosslinking reactive groups of the core-shell type resin microparticles with each other via a polyfunctional crosslinking agent, or a method of crosslinking reactive groups of the core-shell type resin microparticles with reactive groups in a primer layer or a resin layer described below.

[0063] As for the reactive group which the ethylenically unsaturated monomer may have, the description in the section of <Ethylenically unsaturated monomer> in the above <Primer layer> can be cited. When the core-shell type resin microparticles have a ketone group, the preferred content of the ketone group is in the range of 0.05 to 0.3 mmol / g based on the mass of the core-shell type resin microparticles. By introducing in the range of 0.05 to 0.3 mmol / g, crosslinking is formed without inhibiting the fusion of the shell, so that the bonding between particles and between layers becomes stronger, and good color development can be maintained even after various resistance tests such as abrasion resistance tests are performed. In addition, when it is within 0.3 mmol / g, the polymerization stability of the core-shell type resin microparticles is improved and the uniformity of the particle size is improved, resulting in good color development.

[0064] When a reactive group is introduced into the core-shell type resin fine particles, it is preferable to introduce the reactive group into the shell portion, since this makes it possible to more effectively exert the synergistic effect of thermal fusion and crosslinking due to entanglement of polymer chains.

[0065] {Radical polymerization initiator} As the radical polymerization initiator used in the production of the core-shell type resin microparticles, a known oil-soluble polymerization initiator or water-soluble polymerization initiator can be used, and the description in the section on <Ethylenically unsaturated monomer> in the above <Primer layer> can be used.

[0066] {Surfactant} A surfactant is generally used in the production of core-shell type resin particles, and the use of the surfactant can improve the stability and monodispersity of the core-shell type resin particles. The surfactant can be an anionic or nonionic surfactant, and is preferably an anionic surfactant. The description of the surfactant in the above-mentioned section on <Surfactant> in <Primer layer> can be used for these surfactants.

[0067] {Other ingredients} In the production of the core-shell type resin particles, a reducing agent, a buffering agent, a chain transfer agent, and a neutralizing agent can be used as necessary.

[0068] {Characteristics of core-shell type resin particles} The average particle diameter of the core-shell type resin microparticles is preferably 180 to 330 nm. When the average particle diameter is 180 nm or more, the coloring property of the colloidal crystal in the visible light region becomes clear, and a laminate having better coloring property can be obtained. When the average particle diameter is 330 nm or less, the coloring property of the colloidal crystal in the visible light region is excellent, and scattering by the particles is suppressed, resulting in better coloring property. The average particle size in this specification can be measured by dynamic light scattering (measuring device manufactured by Nanotrack UPA Co., Ltd., Microtrack Bell Co., Ltd.), and the peak of the obtained volume particle size distribution data (histogram) is regarded as the average particle size.

[0069] The coefficient of variation (Cv value) of the average particle size of the core-shell type resin fine particles is preferably 30% or less. The coefficient of variation is a value that indicates the uniformity of the particle size, and can be calculated by the following formula. Formula: Coefficient of variation Cv value (%) = standard deviation of particle size / average particle size x 100 [In the formula, the units of standard deviation and average particle size are the same] By arranging highly monodisperse fine particles with a coefficient of variation of 30% or less, the regularity of the particle arrangement is improved, and more vivid and clear structural colors can be expressed.

[0070] The core of the core-shell type resin microparticles preferably has a glass transition point of 60° C. or higher, more preferably in the range of 60° C. to 150° C. When the glass transition point is 60° C. or higher, the shape of the core is prevented from being deformed by the influence of external heat or force, and thus the color development can be better maintained even before and after aging tests at high temperatures.

[0071] The shell of the core-shell type resin microparticles preferably has a glass transition point in the range of -50 to 20°C, more preferably in the range of -30 to 10°C. Within the above range, the voids in the colloidal crystal layer are prevented from being filled by the fusion of the shell. Furthermore, the fusion of the shell is promoted, and the strength of the fused portion is sufficiently improved. This allows the product to exhibit excellent color development, and the color development can be maintained even after various resistance tests such as aging tests and abrasion resistance tests under high temperature conditions. The shell and the core may have multiple glass transition points.

[0072] In the core-shell type resin microparticles, the content of the shell is preferably in the range of 10 to 150% by mass, more preferably in the range of 30 to 70% by mass, based on the mass of the core. Within the above range, the voids in the colloidal crystal layer are prevented from being filled by fusion of the shell. Meanwhile, the fusion of the shell proceeds sufficiently, and the bonds between the core-shell type resin microparticles and between the core-shell type resin microparticles and the layer in contact with the colloidal crystal layer are stronger. This allows the product to exhibit excellent color development, and the color development can be maintained even after various resistance tests such as aging tests under high temperature conditions and abrasion resistance tests are performed.

[0073] [Chromatic pigment] The colloidal crystal layer in the present invention contains a chromatic dye for the purpose of color development and suppression of scattered light. In this specification, "chromatic color" refers to a color that is different from colors such as white and black and has even a slight sense of color. By using a chromatic dye, a laminate with a specific color development can be obtained by combining both the reflected light by the colloidal crystals and the color development derived from the dye. As the chromatic colorant, at least one selected from the group consisting of pigments and dyes can be used. From the viewpoint of film resistance, pigments are preferred. As for the chromatic dye contained in the colloidal crystal layer, the description in the section on chromatic dye in the primer layer above can be used.

[0074] The content of the chromatic dye is preferably in the range of 0.01 to 30% by mass, more preferably in the range of 0.05 to 20% by mass, based on the mass of the core-shell type microparticles. If it is 0.01% by mass or more, the coloring property derived from the chromatic dye is exhibited and scattered light can be suppressed. If it is 30% by mass or less, the arrangement of the core-shell resin microparticles is not disrupted by the chromatic dye, and the effect on structural coloring is small, which is preferable.

[0075] (Pigment dispersion method) The method of incorporating the pigment into the colloidal crystal layer can be appropriately selected from known methods, and the description in the section on "Pigment Dispersion Method" in the above-mentioned "Primer Layer" can be used. From the viewpoint of excellent pigment dispersion stability and film physical properties, the method of (1) using a water-soluble pigment dispersion resin is preferred. For the water-soluble pigment dispersing resin, the description in the section <Water-soluble pigment dispersing resin> in the above <Primer layer> can be used.

[0076] [Formation of colloidal crystal layer] The method for forming the colloidal crystal layer is not particularly limited, but for example, the colloidal crystal layer can be formed by applying a composition for a colloidal crystal layer containing core-shell type resin particles and water onto the primer layer of a substrate having a primer layer. The colloidal crystal layer may be applied in a solid coating, or may form a pattern. The thickness of the colloidal crystal layer is not particularly limited, and from the viewpoints of color development and productivity, it is preferably 3 to 30 μm, and more preferably 5 to 20 μm.

[0077] The colloidal crystal layer composition may contain achromatic black fine particles, hydrophilic solvents, nonionic surfactants, crosslinking agents, and the like for the purpose of improving coatability, coating resistance, and color development, so long as such ingredients do not adversely affect the particle arrangement or the various physical properties of the laminate.

[0078] {Achromatic black particles} The achromatic black particles absorb the scattered light in the colloidal crystal layer to make the color more vivid, so they can be used in combination with chromatic dyes. The description of the achromatic black particles in the above primer layer can be used for the achromatic black particles. The average particle size of the achromatic black fine particles is preferably in the range of 30 to 300 nm. The content of the achromatic black fine particles is preferably in the range of 0.3 to 3 mass % based on the mass of the core-shell type resin fine particles. When the average particle size and the content of the achromatic black fine particles are in the above range, the ordered arrangement of the core-shell type resin fine particles is not hindered and the loss of the core-shell type resin fine particles from the colloidal crystal layer can be suppressed. This makes it possible to maintain good color development even after various resistance tests such as abrasion resistance tests are performed.

[0079] {hydrophilic solvent} For the hydrophilic solvent, the description in the section on <Hydrophilic Solvent> above in <Primer Layer> can be used.

[0080] {Nonionic surfactant} By including a nonionic surfactant in the composition for a colloidal crystal layer, printability is improved without adversely affecting the formation of the colloidal crystal layer, and the color development of the laminate formed is improved. The HLB value of the nonionic surfactant is preferably 10.0 to 19.0. By using a nonionic surfactant having such an HLB value, the leveling property of the composition for a colloidal crystal layer is improved, and the color development of the laminate is improved. The HLB value is a numerical representation of the hydrophilicity and lipophilicity of a material, and the smaller the HLB value, the higher the lipophilicity. In this specification, the HLB value is calculated by the Griffin method shown in Equation 2 below. Equation 2: HLB value = 20 x (sum of hydrophilic moiety formula weights) ÷ (molecular weight of material)

[0081] Examples of such nonionic nonreactive surfactants include polyoxyethylene alkyl ethers (commercially available products include Noigen TDS-120 manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd. and Emulgen 1108 manufactured by Kao Corporation); polyoxyethylene styrenated phenyl ethers (commercially available products include Noigen EA-87, EA-137, and EA-157 manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.); polyoxyethylene sorbitan higher fatty acid esters such as polyoxyethylene sorbitan monolaurate; and polyoxyethylene higher fatty acid esters.

[0082] {Crosslinking agent} There are no particular limitations on the crosslinking agent that may be contained in the colloidal crystal layer composition, and the description in the section on <Crosslinking agent> in the above <Primer layer> can be used. As the crosslinking agent, it is preferable to use a hydrazide crosslinking agent to form a ketone-hydrazide crosslink. Examples of the hydrazide crosslinking agent include adipic acid dihydrazide and a water-soluble resin modified with a multifunctional hydrazide group.

[0083] <Resin layer> The laminate of the present invention may further have a resin layer on the colloidal crystal layer for the purpose of protecting the colloidal crystal layer. By forming the resin layer, the physical properties in various physical property tests such as abrasion resistance and alcohol resistance can be improved.

[0084] The resin constituting the resin layer is not particularly limited, but is preferably an acrylic resin, more preferably a styrene-acrylic resin, from the viewpoint of excellent adhesion to the core-shell type resin particles. In addition, the resin layer is preferably a layer formed by drying aqueous resin particles, not a water-soluble resin or a solvent-based resin, from the viewpoint of suppressing penetration into the colloidal crystal layer.

[0085] The method for producing the aqueous resin microparticles is not particularly limited, and for example, they can be produced by the following emulsion polymerization. First, an aqueous medium and a surfactant are charged into a reaction tank, and the temperature is raised to a predetermined temperature. Meanwhile, water, a surfactant, and an ethylenically unsaturated monomer including a (meth)acrylic monomer are charged into a dropping tank, and an emulsion of the ethylenically unsaturated monomer is prepared by stirring. Then, under a nitrogen atmosphere, a radical polymerization initiator is added while dropping the prepared emulsion into the reaction tank. After the reaction starts, polymer particle nuclei are generated, and the particles gradually grow to form acrylic resin microparticles.

[0086] As for the ethylenically unsaturated monomer that can be used in the production of the aqueous resin particles, the description in the section on <Ethylenically unsaturated monomer> in the above <Primer layer> can be used. In addition, for the radical polymerization initiator, surfactant, and other components that can be used in the production of the aqueous resin microparticles, the descriptions in the sections on <Radical polymerization initiator>, <Surfactant>, and <Other components> in the above-mentioned <Primer layer> can be used.

[0087] The aqueous resin fine particles preferably have a reactive group for forming crosslinks, and an ethylenically unsaturated monomer having a reactive group may be used as the ethylenically unsaturated monomer. The aqueous resin fine particles having a reactive group enable crosslinking within the resin layer and crosslinking between the resin layer and the colloidal crystal layer. The crosslinking within the resin layer further improves the coating strength of the resin layer, and the crosslinking between the resin layer and the colloidal crystal layer further strengthens the bond between the resin layer and the colloidal crystal layer, making it possible to obtain a laminate that can maintain excellent color development even after various resistance tests such as abrasion resistance tests.

[0088] Crosslinking within the resin layer can be introduced by a method of reacting reactive groups of the aqueous resin fine particles with each other, or a method of reacting reactive groups of the aqueous resin fine particles via a polyfunctional crosslinking agent. Crosslinking between the resin layer and the colloidal crystal layer can be introduced by a method of reacting reactive groups of the aqueous resin microparticles and the core-shell type resin microparticles with each other, or a method of reacting reactive groups of the aqueous resin microparticles and the core-shell type resin microparticles via a polyfunctional crosslinking agent. Crosslinking between the resin layer and the adhesive layer can be introduced by a method of reacting reactive groups of the aqueous resin microparticles with reactive groups of the resin contained in the adhesive layer, or a method of reacting reactive groups of the aqueous resin microparticles with the resin contained in the adhesive layer via a polyfunctional crosslinking agent.

[0089] As for the reactive group which the ethylenically unsaturated monomer may have, the description in the section of <Ethylenically unsaturated monomer> in the above <Primer layer> can be cited. When the aqueous resin microparticles contain a ketone group, the preferred content of the ketone group is in the range of 0.05 to 0.3 mmol / g based on the mass of the aqueous resin microparticles. By introducing in the range of 0.05 to 0.3 mmol / g, crosslinking is formed without inhibiting the fusion of the aqueous resin microparticles, so that the coating strength of the resin layer is improved and the colloidal crystal layer and the resin layer are more firmly bound together. This further improves the conformability and coating strength of the coating film, and a laminate that can withstand various resistance tests such as abrasion resistance tests can be obtained.

[0090] The average particle size of the aqueous resin fine particles is preferably in the range of 80 to 300 nm, and the aqueous resin fine particles preferably have a glass transition point in the range of -30 to 30°C. When the average particle size and glass transition point are within the above ranges, the aqueous resin microparticles are filled in the surface layer of the colloidal crystal layer, and the penetration of the resin component into the voids of the colloidal crystal layer is further suppressed. Also, when the average particle size is within the above ranges, the resin layer has excellent film-forming properties, so that a homogeneous resin layer without coating unevenness or cracks can be formed, and good color development and further improvement in coating resistance can be achieved. Furthermore, when the resin layer is disposed between the colloidal crystal layer and the adhesive layer, the penetration of the adhesive component from the adhesive layer can be further suppressed. This makes it possible to obtain a laminate that exhibits excellent color development and is capable of maintaining the excellent color development even after various resistance tests such as aging tests under high temperature conditions and abrasion resistance tests.

[0091] [Formation of resin layer] The method for forming the resin layer is not particularly limited, but for example, the resin layer can be formed by applying a resin composition containing aqueous resin particles and water onto the colloidal crystal layer and drying it as necessary. The aqueous resin particles after drying and film formation are preferably a water-insoluble layer. The thickness of the resin layer is not particularly limited, and is preferably 2 to 50 μm, and more preferably 3 to 20 μm. The above resin composition may contain additives such as chromatic dyes, achromatic black fine particles, hydrophilic solvents, crosslinking agents, etc., for the purpose of improving color development, coatability, and coating resistance, so long as they do not adversely affect the various physical properties of the colloidal crystal layer.

[0092] {Chromatic pigment} The chromatic dye acts to make the color development in the laminate more vivid. In particular, in the case of a reverse printing structure in which the color development is confirmed from the substrate side, the presence of a resin layer having a chromatic dye adjacent to the colloidal crystal layer can make the color development more vivid. As for the chromatic dye, the description in the {Chromatic Dye} section in the above-mentioned <Primer Layer> can be used.

[0093] {Achromatic black particles} The achromatic black fine particles absorb the scattered light within the laminate, making the color of the colloidal crystal coating film clearer. This is particularly effective in reverse printing configurations where the color development is confirmed from the substrate side, as it provides clear color development. As for the achromatic black fine particles, the description in the section on the achromatic black fine particles in the primer layer above can be used.

[0094] {hydrophilic solvent} For the hydrophilic solvent that the resin composition may contain, the description in the section on <Hydrophilic Solvent> in the above <Primer Layer> can be used.

[0095] {Crosslinking agent} The crosslinking agent that may be contained in the resin composition is not particularly limited, and the description in the section on <Crosslinking agent> in the above <Primer layer> can be used.

[0096] <Manufacture of Laminate> The laminate of the present invention is a laminate comprising a substrate, a primer layer, and a colloidal crystal layer in this order, and the method for producing the laminate is not particularly limited, but preferably includes the following steps 1 and 2. When forming each layer, a drying step may be included as necessary. Step 1) A step of applying a primer composition onto a substrate and drying it as necessary to form a primer layer. Step 2) A step of applying a composition for a colloidal crystal layer, which contains core-shell type resin particles and a chromatic color dye, onto the primer layer formed in step 1, and drying as necessary to form a colloidal crystal layer.

[0097] When the laminate has a resin layer, it is preferable to carry out the following step 3 after step 2. Step 3) A step of applying a resin composition containing aqueous resin particles and water onto the colloidal crystal layer formed in step 2, and drying as necessary, to form a resin layer.

[0098] The application method of the primer composition, the composition for the colloidal crystal layer, and the resin composition is not particularly limited and may be appropriately selected from, for example, plateless printing methods such as the inkjet method, spray method, dipping method, and spin coating method; and plate-based printing methods such as offset gravure coater, gravure coater, doctor coater, bar coater, blade coater, flexo coater, and roll coater. The primer composition, the composition for the colloidal crystal layer, and the resin composition may be printed in a solid pattern or may be a pattern layer. When the method includes a drying step, the drying method is not particularly limited and can be appropriately selected from known methods such as heat drying, hot air drying, infrared drying, microwave drying, drum drying, etc. The drying method may be used alone or in combination of two or more, but from the viewpoint of reducing damage to the substrate and drying efficiently, it is preferable to use the hot air drying method. The drying temperature for the primer composition and the resin composition is preferably in the range of 50 to 120°C, and the drying temperature for the colloidal crystal layer composition is preferably in the range of 25 to 80°C.

[0099] [Base material] The substrate is not particularly limited and can be selected from known substrates. Examples of the substrate include thermoplastic resin substrates such as polyvinyl chloride sheet, polyethylene terephthalate (PET) film, polypropylene (PP) film, polyethylene (PE) film, nylon (Ny) film, polystyrene film, and polyvinyl alcohol film; metal substrates such as aluminum foil; glass substrates; and coated paper substrates. Because the laminate of the present invention has a primer layer, it can exhibit excellent substrate conformability, abrasion resistance, water resistance, solvent resistance, and color development even when used with non-polar film substrates such as polyethylene terephthalate films, polypropylene films, and polyethylene films, which have traditionally been difficult to fix due to peeling of the colloidal crystal layer.

[0100] The substrate may have a smooth surface or may have irregularities, and may be transparent, semi-transparent, or opaque. When the colloidal crystal layer is to be viewed from the substrate side, the substrate is preferably transparent. In addition, the substrate may be pre-colored black or the like, or may be partially printed with a pigment ink or the like, in order to make the color development of the colloidal crystals clearer, and may be surface-treated, such as by corona treatment or plasma treatment. These substrates may be used alone or in the form of a laminate of two or more kinds.

[0101] <Thermal recording medium> The laminate of the present invention can be used as a thermal recording medium such as a thermal recording sheet because heat treatment causes the shell of the colloidal crystal layer to fluidize and fill the voids, causing the color of the colloidal crystal layer to fade and resulting in a clear color change. The heat treatment method can be appropriately selected as long as it does not impair the effects of the present invention, and examples of the heat treatment method include a method in which a thermal head of a thermal printer is applied to the laminate to heat it; a method in which laser light is irradiated to cause the achromatic black microparticles in the colloidal crystal layer to absorb the light and heat the adjacent core-shell type resin microparticles; oven heating, microwave heating, and boiling treatment. The image formation by laser is preferred because it can form an image without damaging the substrate, the resin layer, or the non-image forming area. In addition, it is preferred to use an infrared laser because it has little adverse effect on the substrate, the resin forming the primer layer, the core-shell type resin particles, and the resin forming the resin layer. Examples of infrared laser markers include CO2 laser markers (wavelength 10600 nm), YVO4 laser markers (wavelength 1064 nm), YAG laser markers (wavelength 1064 nm), and fiber laser markers (wavelength 1090 nm). The heating temperature can be appropriately changed depending on the design of the core-shell type resin particles, and is preferably in the range of 100 to 200°C, more preferably 120 to 150°C, taking into consideration storage stability, color change during heating, thermal damage to the substrate, etc.

[0102] The thermosensitive recording medium of the present invention may further have another layer within the range that does not impair the effect of the present invention, for example, it may have a hard coat layer and / or an adhesive layer, and may be in a form that is further laminated to another substrate via these. Moreover, these other layers may be disposed on the substrate side or on the colloidal crystal layer side. When the thermosensitive recording medium further has an adhesive layer, it can be used as an adhesive sheet.

[0103] [Adhesive layer] The adhesive layer serves to adhere the laminate of the present invention having a colloidal crystal layer to any adherend. The thickness of the adhesive layer is usually in the range of 5 to 100 μm. The adhesive layer can be formed using a known pressure-sensitive adhesive, and is not particularly limited. The pressure-sensitive adhesive can be appropriately selected depending on the type of the substrate and colloidal crystal layer, and preferably contains at least one resin selected from the group consisting of acrylic resins and urethane resins. The resin forming the adhesive layer preferably has a low content of unreacted components and residual solvents, and an aqueous resin is preferably used. If the content of unreacted components and residual solvents in the resin is low, the influence on the substrate, the colloidal crystal layer, and the resin layer can be suppressed. Here, the aqueous resin refers to a resin that can be dispersed or dissolved in an aqueous medium. The aqueous medium refers to an aqueous dispersion medium or an aqueous solvent, and includes a dispersion medium or solvent that is miscible with water in addition to water. The adhesive layer can contain various additives such as a crosslinking agent and a tackifier for the purpose of adhesive properties. EXAMPLES

[0104] The present invention will be specifically described below with reference to examples and comparative examples. In the examples and comparative examples, "parts" and "%" mean "parts by mass" and "% by mass" unless otherwise specified. In addition, the numerical values ​​in the tables represent "parts" unless otherwise specified, and blanks mean that no compound is added.

[0105] [Acid value] The acid value was calculated by potentiometric titration of the dried resin with potassium hydroxide-ethanol solution in accordance with JIS K2501. An automatic titrator COM-1600 manufactured by Hiranuma Sangyo Co., Ltd. was used for the titration.

[0106] [Glass transition temperature (Tg)] The glass transition point was measured by DSC (differential scanning calorimeter manufactured by TA Instruments Co., Ltd.). Specifically, about 2 mg of a sample obtained by drying the resin was weighed on an aluminum pan, the aluminum pan was set in a DSC measurement holder, and the glass transition point was obtained by reading the baseline shift (inflection point) toward the endothermic side of the DSC curve obtained under the temperature increase condition of 5° C. / min.

[0107] [Average particle size] The dispersion of the core-shell type resin particles was diluted 500 times with water, and about 5 ml of the diluted solution was measured by dynamic light scattering measurement (measuring device manufactured by Nanotrack UPA Co., Ltd., Microtrack Bell Co., Ltd.). The peak of the obtained volume particle size distribution data (histogram) was taken as the average particle size. The coefficient of variation Cv value, which indicates the variation in particle size, was calculated from the following formula. Cv value% = Standard deviation of particle size / Average particle size x 100

[0108] <Production of Water Dispersion of Resin Constituting Primer Layer> [Production Example 1] In a reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, and a reflux condenser, 68.9 parts of ion-exchanged water and 0.25 parts of a 20% aqueous solution of Aqualon KH-10 manufactured by Daiichi Kogyo Seiyaku Co., Ltd. as a reactive surfactant were charged. Separately, 7.5 parts of styrene, 10.0 parts of benzyl methacrylate, 25.0 parts of methyl methacrylate, 16.0 parts of 2-ethylhexyl acrylate, 38.0 parts of n-butyl acrylate, 3.0 parts of methacrylic acid, 0.5 parts of 3-methacryloxypropyltriethoxysilane, 4.8 parts of a 20% aqueous solution of KH-10, and 40.4 parts of ion-exchanged water were mixed and stirred in advance to prepare an emulsion of ethylenically unsaturated monomers, and 3% of the emulsion was further added to the reaction vessel. After the internal temperature was raised to 80°C and the mixture was fully substituted with nitrogen, 2.0 parts of a 5% aqueous solution of potassium persulfate was added as an initiator to initiate emulsion polymerization. While maintaining the internal temperature at 80°C, the remaining emulsion of ethylenically unsaturated monomers and 2.0 parts of a 5% aqueous solution of potassium persulfate were added dropwise over 3 hours, and the mixture was allowed to react for another 4 hours to obtain an aqueous dispersion of resin fine particles. After the reaction was completed, 2.4 parts of 25% ammonia water was added to neutralize, and the solid content of the aqueous dispersion of resin fine particles was adjusted to 45.0% with ion-exchanged water. The acid value of the resin was 19.5 mgKOH / g, and Tg was -8.8°C.

[0109] [Manufacturing Examples 2 to 6] A water dispersion of resin fine particles was obtained in the same manner as in Production Example 1, except that the blending composition was changed to that shown in Table 1. After the reaction was completed, 25% ammonia water was added to the resin so that the amount was equimolar to the carboxyl group in the resin, and neutralization was performed. The solid content of the water dispersion of resin fine particles was adjusted to 45.0%. The acid value and Tg of the obtained resin were measured in the same manner as in Production Example 1.

[0110] [Production Example 7] In a reaction vessel equipped with a stirrer, a thermometer, two dropping funnels, and a reflux condenser, 185.0 parts of ion-exchanged water, 42.9 parts of JONCRYL67 (styrene acrylic resin manufactured by BASF: weight average molecular weight (Mw) 12,500, acid value 213 mgKOH / g) as a polymer dispersant, and 11.1 parts of 25% ammonia water were charged, and the temperature was raised while stirring to dissolve the polymer dispersant. After further raising the temperature to 80°C under nitrogen reflux, in one of the two dropping funnels, a mixture of 14.0 parts of styrene, 15.0 parts of n-butyl methacrylate, 30.0 parts of 2-ethylhexyl acrylate, 10.0 parts of cyclohexyl methacrylate, 30.0 parts of n-butyl acrylate, and 1.0 parts of glycidyl methacrylate was dropped over 2 hours. From the other, 3.5 parts of a 20% aqueous solution of ammonium persulfate was dropped over 2 hours. After the completion of the dropping, the reaction was continued for another 5 hours to obtain an aqueous dispersion of resin particles. After the reaction was completed, the solid content of the resin particle dispersion was adjusted to 40.0% with ion-exchanged water. The acid value of the obtained resin was 63.9 mg KOH / g, and Tg was -1.3°C.

[0111] [Production Example 8] A water dispersion of resin fine particles was obtained in the same manner as in Production Example 7, except that the amount of JONCRYL67 added was changed to 53.8 parts and 25% ammonia water was changed to 13.9 parts. After the reaction was completed, the solid content of the resin fine particle dispersion was adjusted to 40.0% with ion-exchanged water. The acid value of the obtained resin was 74.6 mg KOH / g and Tg was 3.4°C.

[0112] [Table 1]

[0113] [Production Example 9] Into a reaction vessel equipped with a stirrer, a thermometer, and a reflux condenser, 19.6 parts of PTG-2000SN (polytetramethylene glycol manufactured by Hodogaya Chemical; functionality 2, hydroxyl value 57.0 mgKOH / g, molecular weight 2,000) and 20 parts of P-2011 (3-methyl-1,5-pentanediol / adipic acid / terephthalic acid-based polyester polyol manufactured by Kuraray; functionality 2, hydroxyl value 55.0 mgKOH / g, molecular weight 2,000) were added as polyol. The following ingredients were charged: 1.3 parts of C-2090 (polycarbonate polyol manufactured by Kuraray; functionality 2, hydroxyl value 56.0 mg KOH / g, molecular weight 2,000) 91.6 parts of dimethylolbutanoic acid, 19.7 parts of isophorone diisocyanate as a polyisocyanate, 48.8 parts of methyl ethyl ketone as a solvent, and 10.0 parts of dipropylene glycol dimethyl ether, and the temperature was raised to 78°C with stirring under a nitrogen atmosphere. 0.02 parts of titanium diisopropoxybis(ethylacetoacetate) was added thereto as a catalyst, and the mixture was allowed to react for 6 hours to obtain a urethane prepolymer having isocyanate groups at both ends. After adding 13.5 parts of triethylamine as a neutralizing agent, 400 parts of ion-exchanged water and 2.4 parts of ethylenediamine as a chain extender were added, and the phase was inverted to an aqueous phase while removing the solvent under reduced pressure conditions. The chain extension reaction of the isocyanate group was promoted in the aqueous medium to prepare an aqueous dispersion of urethane resin with a solid content of 30.0%. The acid value of the obtained resin was 37.4 mgKOH / g, and Tg was 94.0°C.

[0114] [Examples 10 and 11] A water dispersion of a urethane resin was obtained in the same manner as in Production Example 9, except that the blending composition was changed to that shown in Table 2. The solid content of the water dispersion was adjusted to 30.0%. The acid value and Tg of the obtained resin were measured in the same manner as in Production Example 9.

[0115] [Table 2]

[0116] [Production Example 12] In a reaction vessel equipped with a stirrer, a thermometer, and a reflux condenser, 100 parts of Auroren 350S (manufactured by Nippon Paper Industries; maleic anhydride modified polypropylene-polyethylene copolymer) as a solid olefin resin, 100 parts of toluene, and 30.0 parts of Noigen TDS-120 (manufactured by Daiichi Kogyo Seiyaku Co., Ltd. polyoxyethylene tridodecyl ether HLB14.8) as a low molecular weight surfactant were added, and the temperature was raised to 100°C to dissolve the resin. After confirming that it was completely dissolved, 5.0 parts of dimethylaminoethanol and 600.0 parts of ion-exchanged water were added as a neutralizing agent. Thereafter, while removing the solvent under reduced pressure conditions, phase inversion to the aqueous phase was performed, and an aqueous dispersion of olefin resin with a solid content of 30.0% was obtained. The acid value of the obtained aqueous resin was 24.0 mgKOH / g, and Tg was -20°C.

[0117] <Preparation of aqueous dispersion of core-shell type resin particles> [Production Example 13] In a reaction vessel equipped with a stirrer, thermometer, dropping funnel, and reflux condenser, 95.0 parts of ion-exchanged water and 1.5% of the emulsion of the first stage ethylenically unsaturated monomer, which was prepared by mixing and stirring 97.0 parts of styrene, 2.0 parts of acrylic acid, 1.0 parts of 3-methacryloxypropyltrimethoxysilane, 5.0 parts of a 20% aqueous solution of Aqualon KH-10 manufactured by Daiichi Kogyo Seiyaku Co., Ltd., and 39.1 parts of ion-exchanged water, were further added. The internal temperature of the reaction vessel was raised to 70°C and sufficiently substituted with nitrogen, and then 5.7 parts of a 2.5% aqueous solution of potassium persulfate was added as an initiator to start polymerization. The internal temperature was raised to 80°C and maintained at the same temperature, while the remaining emulsion of the first stage ethylenically unsaturated monomer and 4.0 parts of a 2.5% aqueous solution of potassium persulfate were added dropwise over a period of 2 hours to react, synthesizing core particles. 20 minutes after the completion of the first-stage dropping, the dropping of the emulsion of the second-stage ethylenically unsaturated monomer, which was prepared by mixing and stirring 15.0 parts of methyl methacrylate, 26.1 parts of n-butyl acrylate, 0.9 parts of acrylic acid, 2.1 parts of a 20% aqueous solution of KH-10, and 16.8 parts of ion-exchanged water, was started. The reaction was further advanced by dropping the emulsion of the second-stage ethylenically unsaturated monomer and 2.1 parts of a 2.5% aqueous solution of potassium persulfate over 2 hours while keeping the internal temperature at 80°C, to obtain an aqueous dispersion of core-shell type resin particles with a solid content of 45.0%. The average particle size of the obtained core-shell type resin particles was 253 nm, the Cv value was 25.7%, and the Tg of the core portion was 100.1°C and the Tg of the shell portion was -12.5°C.

[0118] [Examples 14-26] A water dispersion of core-shell type resin microparticles was obtained in the same manner as in Production Example 13, except that the blending composition was changed to that shown in Table 3. The emulsion of ethylenically unsaturated monomer was prepared by adding water so that the concentration of ethylenically unsaturated monomer in the emulsion was 69.0% and the concentration of surfactant was 0.69%. The 2.5% aqueous solution of potassium persulfate, which was dropped simultaneously with the emulsion, was added in an amount equivalent to 0.1% in solid form relative to the total amount of ethylenically unsaturated monomer to be dropped. In Production Examples 18, 19, 20, and 26, the reactive surfactant was changed to AR-10 (anionic reactive surfactant) manufactured by Daiichi Kogyo Seiyaku, and the amount of the emulsion of ethylenically unsaturated monomer in the first stage, which was divided and charged into the reaction tank, was changed from 1.5% to 3.3%, 4.1%, 2.1%, and 3.3%, respectively. The average particle size, Cv value, Tg of the core part, and Tg of the shell part of the obtained core-shell type resin microparticles were measured.

[0119] <Preparation of water dispersion of non-core-shell type resin microparticles> [Production Example 27] A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, and a reflux condenser was charged with 68.9 parts of water, and 3% of the emulsion of ethylenically unsaturated monomers, which had been previously mixed and stirred with 85.0 parts of styrene, 5.0 parts of benzyl methacrylate, 7.0 parts of 2-ethylhexyl acrylate, 2.0 parts of acrylic acid, 1.0 parts of 3-methacryloxypropyltriethoxysilane, 5.0 parts of a 20% aqueous solution of Aqualon KH-10, and 40.4 parts of water, was further added. After the internal temperature was raised to 70°C and sufficiently substituted with nitrogen, 2.0 parts of a 5% aqueous solution of potassium persulfate was added as an initiator to start emulsion polymerization. The internal temperature was raised to 80°C and the temperature was maintained while the remaining emulsion of ethylenically unsaturated monomers and 2.0 parts of a 5% aqueous solution of potassium persulfate were dropped over 3 hours, and the reaction was continued for another 4 hours to obtain an aqueous dispersion of resin fine particles with a solid content of 45.0%. The average particle size of the obtained resin particles was 201 nm, the coefficient of variation Cv was 25.8%, and Tg was 76.9°C.

[0120] [Table 3]

[0121] <Preparation of Water Dispersion of Water-Based Resin Fine Particles Constituting Resin Layer> [Production Example 28] A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, and a reflux condenser was charged with 68.9 parts of ion-exchanged water, and 3% of the emulsion of ethylenically unsaturated monomers was further added, which was previously mixed and stirred with 15.0 parts of styrene, 30.0 parts of methyl methacrylate, 16.0 parts of 2-ethylhexyl acrylate, 35.0 parts of n-butyl acrylate, 2.0 parts of methacrylic acid, 1.0 parts of acrylic acid, 1.0 parts of 3-methacryloxypropyltriethoxysilane, 5.0 parts of a 20% aqueous solution of Aqualon KH-10, and 40.4 parts of ion-exchanged water. The internal temperature was raised to 70°C and sufficiently replaced with nitrogen, and then 2.0 parts of a 5% aqueous solution of potassium persulfate was added as an initiator to start emulsion polymerization. The internal temperature was raised to 80°C, and while maintaining the temperature, the remaining emulsion of ethylenically unsaturated monomer and 2.0 parts of a 5% aqueous solution of potassium persulfate were dropped over 3 hours, and the reaction was continued for another 4 hours to obtain an aqueous dispersion of aqueous resin particles with a solid content of 45.0%. The average particle size of the obtained aqueous resin particles was 196 nm, and Tg was -2.4°C.

[0122] [Examples 29-36] A water dispersion of aqueous resin microparticles was prepared in the same manner as in Production Example 28, except that the blending composition was changed to that shown in Table 4. In Production Examples 29, 32, 33, and 34, the emulsion of ethylenically unsaturated monomers charged in separate portions to the reaction tank was changed from 3% to 1.5%, 5%, 1.5%, and 1.3%, respectively. In Production Example 35, 1.0 part of KH-10 was additionally charged to the reaction tank before the start of the reaction, and in Production Example 36, 1.3 parts of KH-10 was additionally charged. The average particle size and Tg of the obtained aqueous resin microparticles were measured.

[0123] [Table 4]

[0124] <Adjustment of resin for dispersing water-soluble pigment> [Production Example 37) A reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer was charged with 93.4 parts of triethylene glycol monomethyl ether and replaced with nitrogen gas. The reaction vessel was heated to 110°C, and a mixture of 35.0 parts of lauryl methacrylate, 35.0 parts of styrene, 30.0 parts of acrylic acid, and 6.0 parts of V-601 (oil-soluble azo polymerization initiator manufactured by Wako Pure Chemical Industries, Ltd.) was added dropwise over 2 hours to carry out a polymerization reaction. After the dropwise addition, the mixture was reacted at 110°C for another 3 hours, and then 0.6 parts of V-601 was added, and the reaction was continued at 110°C for another 1 hour to obtain a solution of dispersion resin 1. The weight average molecular weight of dispersion resin 1 was about 16000. After cooling to room temperature, 37.1 parts of dimethylaminoethanol was added to neutralize. This is the amount that neutralizes 100% of acrylic acid. Furthermore, 200 parts of water was added to make it aqueous. Next, water was added so that the non-volatile content became 20% to obtain an aqueous solution of a water-soluble pigment dispersing resin.

[0125] <Preparation of primer composition> [Production Example 38] A primer composition was prepared by adding 2.0 parts of isopropyl alcohol to 100 parts of the aqueous dispersion of the resin obtained in Production Example 1 and stirring the mixture.

[0126] [Examples 39-51] A primer composition was prepared in the same manner as in Production Example 38, except that the formulation was changed to that shown in Table 5. For Production Example 51, the organic pigment used was added and adjusted in the following manner. 20 parts of LIONOL YELLOW TT-1402G (manufactured by Toyo Color Co., Ltd.), 30 parts of the water-soluble pigment dispersion resin (copolymer of lauryl methacrylate / styrene / acrylic acid = 35 / 35 / 30, non-volatile content 20%) obtained in Production Example 37, and 30 parts of ion-exchanged water were dispersed in a paint conditioner for 2 hours to obtain a yellow pigment dispersion. Using the obtained yellow pigment dispersion, a yellow pigment dispersion was added and stirred so that the content of LIONOL YELLOW TT-1402G (manufactured by Toyo Color Co., Ltd.) was 5 parts per 100 parts of the aqueous dispersion of resin fine particles, and a primer composition was prepared.

[0127] [Table 5]

[0128] <Preparation of Composition for Colloidal Crystal Layer> [Example 52] 20 parts of LIONOL YELLOW TT-1402G (manufactured by Toyocolor Co., Ltd.), 30 parts of the water-soluble pigment dispersion resin obtained in Production Example 37 (copolymer of lauryl methacrylate / styrene / acrylic acid=35 / 35 / 30, non-volatile content 20%), and 30 parts of ion-exchanged water were dispersed in a paint conditioner for 2 hours to obtain a yellow pigment dispersion. The obtained yellow pigment dispersion was added and stirred so that the content of the yellow pigment was 5 parts per 100 parts of the aqueous dispersion of resin fine particles obtained in Production Example 13, to prepare a resin composition for colloidal crystals.

[0129] [Example 53] LIONOL YELLOW TT-1402G (manufactured by Toyocolor Co., Ltd.) was added in an amount of 5 parts per 100 parts of the aqueous dispersion of resin fine particles obtained in Production Example 13, and dispersed in a paint conditioner for 2 hours to prepare a resin composition for colloidal crystals.

[0130] [Manufacturing Examples 54-61, 63-80] Compositions for colloidal crystal layer were prepared in the same manner as in Production Example 52, except that the blending compositions and pigment types were changed to those shown in Tables 6 and 7.

[0131] [Manufacturing Example 62] A primer composition was prepared by adding 2.0 parts of Supermonas UR (manufactured by Yaegaki Fermentation Engineering Co., Ltd.) to 100 parts of the aqueous dispersion of the resin fine particles obtained in Production Example 13 and stirring the mixture.

[0132] [Table 6]

[0133] [Table 7]

[0134] <Preparation of Resin Composition> [Example 81] To 100 parts of the water dispersion of the aqueous resin particles obtained in Production Example 28, 0.2 parts of isopropyl alcohol was added and stirred to prepare a resin composition.

[0135] [Examples 82-91] A resin composition was prepared in the same manner as in Production Example 81, except that the blending composition was changed to that shown in Table 8. For Production Example 91, a resin composition was prepared by adding LIONOL YELLOW TT-1402G (manufactured by Toyocolor Co., Ltd.) to the yellow pigment dispersion obtained in Production Example 52 so that the content was 5 parts per 100 parts of the aqueous dispersion of resin fine particles, and stirring the mixture.

[0136] [Table 8]

[0137] <Preparation of Laminate> [Example 1] The primer composition of Production Example 38 was applied to the corona-treated surface of a biaxially oriented polypropylene (OPP) film (Futamura FOR, thickness 20.0 μm) using a bar coater so that the dry thickness was 3 μm, and then dried in an oven at 50° C. for 3 minutes to form a primer layer. Next, the colloidal crystal layer composition of Production Example 52 was applied to the primer layer using a bar coater so that the dry thickness was 9 μm, and then dried at 50° C. for 3 minutes to obtain a laminate having a configuration of OPP / primer layer / colloidal crystal layer.

[0138] [Examples 2 to 54, Comparative Examples 1 to 3, and Comparative Example 5] Laminates were obtained in the same manner as in Example 1, except for changing the combinations shown in Tables 9 to 12. Coating was performed by changing the bar coater so that the dry film thickness of the composition for colloidal crystal layer was 3 μm in Example 53 and 30 μm in Example 54. In Examples 40 to 52 and Comparative Examples 1 to 4, the resin composition was applied onto the colloidal crystal layer with a bar coater so that the dry film thickness was 10 μm, and then dried in an oven at 70° C. for 3 minutes to form a resin layer. In Comparative Example 3, the composition for colloidal crystal layer was applied directly to the substrate without providing a primer layer.

[0139] [Comparative Example 4] An aqueous solution of polyvinyl alcohol (Poval 22-88, manufactured by Kuraray Co., Ltd.; solids content 20.0%) was applied onto the colloidal crystal layer of the laminate of Example 1 using a bar coater and dried in an oven at 70°C for 3 minutes, replacing the air in the voids in the colloidal crystal layer with a resin component.

[0140] <Evaluation of the laminate> The resulting laminate was checked for air voids in the colloidal crystal layer. The resulting laminate was also subjected to the following evaluations. The results are shown in Tables 9 to 12.

[0141] [Identification of voids in colloidal crystal layers] The cross section of the obtained laminate was observed with a scanning electron microscope (JEOL JSM-7800F) to confirm the presence or absence of voids in the colloidal crystal layer. As a result, it was confirmed that the voids in the laminate of Comparative Example 4 were completely filled with resin. It was confirmed that the voids in the colloidal crystal layer of the other laminates were not completely filled with the resin component, and the colloidal crystal layer had voids.

[0142] [Color development from low angles] The color development of the laminate was evaluated visually from a position of 70°, with the angle when viewed from the front of the substrate being 0° and the angle when viewed from the side of the substrate being 90°. In Examples 40 to 52, the evaluation was performed from the substrate side, and in the other examples, the evaluation was performed from the colloidal crystal layer side. S: The color of the laminate can be seen very clearly (very good) A: The color of the laminate can be clearly confirmed (good) B: The color of the laminate can be slightly confirmed (usable). C: No color development can be confirmed in the laminate (unusable)

[0143] [Reflectance measurement (color development due to structural color)] The reflectance spectrum of the laminate was measured in the wavelength range of 250 to 850 nm using an ultraviolet-visible near-infrared spectrophotometer (V-770D manufactured by JASCO Corporation, integrating sphere unit ISN-923). The reflectance at each wavelength is a relative reflectance measured using a standard white board with a known reflectance (SRS-99-010 manufactured by Labsphere) as a reference. In Examples 40 to 52, the measurements were taken from the substrate side, and the other examples were measured from the colloidal crystal layer side. For the obtained reflectance spectrum, the difference (ΔR) between the maximum reflectance due to the structural color and the baseline reflectance not due to the structural color was calculated. The larger ΔR, the better the color development. The obtained ΔR was evaluated according to the following criteria. S;△R is 30% or more (very good) A: △R is 20% or more and less than 30% (good) B: △R is 10% or more and less than 20% (usable) C: △R is less than 10% or the reflectance peak due to structural color cannot be identified (unusable)

[0144] [Storage stability of laminate] After leaving the laminate at room temperature for 6 months, the reflectance spectrum was measured in the same manner as in the above-mentioned reflectance measurement. The reflectance spectra before and after the aging were compared to calculate the rate of change (decrease) in the maximum reflectance. The larger the decrease, the more the colloidal crystals faded. The decrease was evaluated according to the following criteria. S: The change in maximum reflectance is less than 3% (very good) A: The change in maximum reflectance is 3% or more and less than 5% (good) B: The change in maximum reflectance is 5% or more and less than 10% (usable) C: The change in maximum reflectance is 10% or more (not suitable for use)

[0145] [Substrate conformity] A square test piece measuring 2 cm x 2 cm was cut out from the obtained laminate, and the laminate was rubbed 20 times and the change in appearance was observed. The evaluation criteria were as follows: S: No peeling or scratches at all. (Very good) A: Slight peeling or scratches (less than 1% of the entire test piece) (good) B: Slight peeling or scratches (area is 1% to less than 5% of the entire test piece) (usable) C: Slight peeling or scratches (over 5% of the entire test piece) (unusable)

[0146] [Adhesion to substrate] A cellophane tape (18 mm wide, manufactured by Nichiban Co., Ltd.) was applied to the prepared laminate (1 cm x 1 cm), and slowly peeled off in the vertical direction to evaluate the adhesion to the substrate from the ratio of the peeled area. The evaluation criteria are as follows. S: No peeling at all. (Very good) A: Slight peeling (less than 5% of the entire test piece is peeled off) (good) B: Peeling occurred (peeled area is 5% or more, but less than 10% of the entire test piece) (usable) C: Peeling occurred (peel area is 10% or more of the entire test piece) (unusable)

[0147] [Abrasion resistance] The obtained laminate was placed on a smooth glass plate with the coated side facing up, and a square area of ​​2 cm x 2 cm was rubbed back and forth with the pad of a finger 40 times, and the presence or absence of scratches or peeling was observed. The evaluation criteria were as follows. S: No scratches or peeling. (Very good) A: Slight peeling (less than 1% of the entire test piece is peeled off) (good) B: Peeling occurred (peeled area is 1% or more, but less than 3% of the entire test piece) (usable) C: Peeling occurred (peel area is 3% or more of the entire test piece) (unusable)

[0148] [Rubbing resistance] A test piece (1 cm x 1 cm) of the obtained laminate was rubbed 20 times with a cotton swab soaked in water or ethanol, and the laminate was observed for its susceptibility to scratches and peeling. The evaluation criteria were as follows: S: No scratches or peeling (very good) A: Slight peeling (less than 5% of the entire test piece is peeled off) (good) B: Peeling occurred (peeled area is 5% or more, but less than 10% of the entire test piece) (usable) C: Peeling occurred (peel area is 10% or more of the entire test piece) (unusable)

[0149] [Water and solvent resistance] The obtained laminate was cut into a test piece of 2 cm x 2 cm, immersed in water or an ethanol solution for 3 minutes, then removed and allowed to air dry at room temperature, and the appearance of the laminate was checked for changes. The evaluation criteria were as follows: S: No peeling or scratches (very good) A: Slight peeling or scratches (less than 1% of the entire test piece) (good) B: Slight peeling or scratches (area is 1% to less than 5% of the entire test piece) (usable) C: Peeling or scratches have occurred (over 5% of the entire test piece) (unusable)

[0150] [Color change when heated] The laminate was attached to a piece of A4 size white paper with tape, and a 2 cm x 2 cm square was heated using a thermal printer equipped with a thermal head (Brother Industries, PocketJet PJ-673) with the density set at 5 to form an image. Furthermore, a square image was formed using a Keyence YVO4 laser marker MD-V9600A (wavelength 1064 nm) equipped with an infrared laser under conditions of a laser power of 30% and a scan speed of 2000 mm / sec. Heating with a thermal head was performed from the colloidal crystal layer side, and irradiation with an infrared laser was performed from the substrate side. The laminate on which the image was formed was visually observed. The reflection spectrum was measured for the heated portion (image portion) and the non-heated portion (non-image portion) in the same manner as in the above-mentioned reflectance measurement. The reflection spectra of the heated portion and the non-heated portion were compared, and the rate of change (decrease rate) of the maximum reflectance was calculated and evaluated according to the following criteria. The larger the rate of change, the more obvious the color change caused by the heat treatment. When an image could not be formed due to reasons such as peeling of the colloidal crystal layer during image formation, the recording medium was judged as unusable, and was also judged as unusable for the subsequent evaluations. S: The image outline is clear and the change in maximum reflectance is 50% or more (very good) A: The image outline is clear and the change in maximum reflectance is 30% or more but less than 50% (good) B: The image outline is clear and the change in maximum reflectance is 10% or more and less than 30% (usable) C: The image outline is unclear, the change in maximum reflectance is less than 10%, or image formation is not possible (unusable).

[0151] [Table 9]

[0152] [Table 10]

[0153] [Table 11]

[0154] [Table 12]

[0155] The laminates and thermosensitive recording medium of the present invention exhibited excellent structural color and color development from all angles in thin films, had excellent long-term storage stability, and showed clear color changes before and after heating. They also had excellent resistance to various films. In particular, the laminates of Examples 40 to 52 having a resin layer on a colloidal crystal layer had excellent rubbing resistance (ethanol) and solvent resistance. [Industrial Applicability]

[0156] The laminate of the present invention is a thin film that exhibits excellent structural color and color development that can be seen from any angle, has excellent storage stability, exhibits a clear color change when heated, and has excellent resistance to various films. Therefore, in addition to imparting design features to heat-sensitive labels, stickers, etc., it can be used in a wide range of applications, such as security devices, optical filters, display elements, optical waveguides, optical resonators, and optical switches. [Explanation of symbols]

[0157] 1 Colloidal crystal layer (close-packed structure) 2 Primer layer 3 Base material 4. Core-shell type resin particles 5. Shell 6 cores 7 void 8 Chromatic pigments 9 Colloidal crystal layer after heating (loosely packed structure) 10. Matrix

Claims

1. A laminate in which a substrate, a primer layer, and a colloidal crystal layer are laminated in this order, the colloidal crystal layer has a structure in which core-shell type resin fine particles are arranged and has voids, and contains a chromatic color dye; the core-shell type resin fine particles are polymers of ethylenically unsaturated monomers and have a coefficient of variation (Cv value) of average particle size of 30% or less; The laminate, wherein the primer layer contains at least one resin selected from the group consisting of acrylic resins, urethane resins, and polyolefin resins.

2. 2. The laminate according to claim 1, wherein the core-shell type resin fine particles contain a shell in a range of 10 to 150% by mass relative to the mass of the core.

3. 3. The laminate according to claim 1, wherein the core has a glass transition point of 60°C or higher, and the shell has a glass transition point in the range of -50 to 20°C.

4. 4. The laminate according to claim 1, wherein the primer layer is a layer containing at least one resin selected from the group consisting of acrylic resins and urethane resins.

5. The laminate according to claim 4, wherein the resin has a glass transition point in the range of -30 to 70°C.

6. 6. The laminate according to claim 1, wherein the colloidal crystal layer contains the chromatic dye in an amount of 0.01 to 30% by mass based on the mass of the core-shell resin fine particles.

7. The laminate according to any one of claims 1 to 6, wherein the chromatic colorant is an organic pigment.

8. 8. The laminate according to claim 1, wherein the colloidal crystal layer further contains colorless black fine particles.

9. A thermosensitive recording medium comprising the laminate according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Record article, recording method, recording device

    JP2001329197A

  • Resin particle for making photonic crystal structure and photonic crystal film obtained from the same

    JP2008083545A

  • Electronic apparatus

    JP2008309933A

  • Structural color flake pigment and method for producing structural color flake pigment

    JP2010024289A

  • Color-developing flake material and method for producing the same

    JP2011102216A